A survey of radiation level in part B of Singapore - Luo, Yunwei (Nanyang Technological University, 2013)
In today's electricity dependent society, talks of nuclear power as an alternative for limited fossil fuels are becoming more prevalent. The recent tragedy that struck Fukushima has also increased public awareness of environmental radiation contamination and about radiation level. This study aims to survey radiation levels of Singapore, to obtain radiation readings at localized areas within the island that is currently not available. A weighted average will also be calculated as an indication to what level of radiation people in Singapore are being exposed to. From the results, Singapore is in no apparent danger from threat due to radiation levels. The weighted average of 1.20 mSv/yr (0.14 μSv/h) obtained for the island is below the global average of roughly 2.4 mSv/yr background radiation. Based on the findings, it appears that readings taken at locations near water bodies are lower than those taken at other locations in the same area. Relationship for buildings and radiation levels however proved to be inconclusive and requires further studies. Due to the inherent complexity of radiation measurement, it is recommended that further studies be carried to confirm propositions mentioned in the report.